Konsep Teologi Perspektif Para Rasul - Suharsono (STIT Muhammadiyah Paciran Lamongan, 2022)
Every Muslim is required to believe that Islam is the true religion. Even though, the prohibition against demeaning other religions has to be carried out. Moreover, it hurts the adherents of other religions outside Islam. The humiliate attitude towards other religions and faith actually shows that Islam is not a noble religion. Whereas the command of Allah SWT in the Qur’an and the spirit brought by the prophet Muhammad SAW is rahmatan lil ‘alamin (the mercy for the whole world).Muslims make the prophet Muhammad SAW as the role model in social life especially in religion. He was the role model of a leader who had charismatic character and able to made peaceful and pleasant feelings for people he led even though they had different faith. This shows that there is no compulsion in having religion. People are free to choose their religion and faith which means that there is no arrogance in theology.In theology, many groups emerged, and each of them brought their own arguments. However the clear concept in Islam’s view is the theology which is based on the genuineness of teachings brought by the Prophets. So, no wonder if all emerged groups claimed that their opinion was the most correct arguments, that is the Ahlu Sunnah Waljama’ah.